Pengaruh Pemberian Abu Boiler Kelapa Sawit Terhadap Pertumbuhan Semai Mahoni (Swietenia mahagoni) pada Media Gambut - Pebriandi; Fadli, Zulkhoiri; Mardhiansyah, Muhammad; Darlis, Viny Volcherina; Somadona, Sonia; Sribudiani, Evi; Nugraha, Lefdi Agung; Irfani, Ewi; Suhada, Nur (Jurnal Ilmu Ilmu Kehutanan, 2025)
Swietenia mahagoni can grow on marginal land and is suitable for use as a revegetation plant. Peat is classified as marginal soil due to its high organic acid content and low levels of macronutrients. One approach to improving the productivity of peat soil is the application of ameliorants, one of which is oil palm boiler ash. This study aimed to evaluate the effect of mixing peat with oil palm boiler ash and to determine the optimal composition of this mixture for the growth of mahogany seedlings. A completely randomized design (CRD) was employed, consisting of five treatments with four replications, resulting in a total of 20 experimental units. The planting media compositions tested were: P0 = 100% peat soil (control), P1 = 10% boiler ash + 90% peat soil, P2 = 15% boiler ash + 85% peat soil, P3 = 20% oil palm boiler ash + 80% peat soil, and P4 = 25% oil palm boiler ash + 75% peat soil. Data were analyzed using SPSS version 26.0. The application of oil palm boiler ash had a significant effect on the growth of mahogany seedlings. The optimal composition was 15% boiler ash and 85% peat, which resulted in an average seedling height increase of 10.01 cm and an average dry weight of 6.61 g.